2022
DOI: 10.1186/s13287-022-02832-0
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin treatment improves human umbilical cord mesenchymal stem cell therapy in a mouse model of type II diabetes mellitus via the PI3K/AKT signaling pathway

Abstract: Background Mesenchymal stem cells (MSCs) are promising candidates for tissue regeneration and disease treatment. However, long-term in vitro passaging leads to stemness loss of MSCs, resulting in failure of MSC therapy. This study investigated whether the combination of melatonin and human umbilical cord mesenchymal stem cells (hUC-MSCs) was superior to hUC-MSCs alone in ameliorating high-fat diet and streptozocin (STZ)-induced type II diabetes mellitus (T2DM) in a mouse model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…This pathway is not only a key regulator of early embryonic development but also closely connected with the development of insulin resistance. [18][19][20] Insulin resistance is a disorder of glucose metabolism that plays a crucial role in T2DM. [21] The activation of the PI3K/AKT signaling pathway could improve insulin sensitivity and alleviate T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is not only a key regulator of early embryonic development but also closely connected with the development of insulin resistance. [18][19][20] Insulin resistance is a disorder of glucose metabolism that plays a crucial role in T2DM. [21] The activation of the PI3K/AKT signaling pathway could improve insulin sensitivity and alleviate T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Under the effect of melatonin, activated MT2 receptors are coupled with G i/o , leading to the activation of the PLCγ/ PKC pathway 141 (Figure 2B). Moreover, melatonin promotes the activation of the PI3K signaling pathway in different cell types [142][143][144][145][146] (Figure 2C). PI3K can enhance antigen-mediated Ca 2+ mobilization by recruiting PLCγ to the plasma membrane, where PLCγ is subsequently phosphorylated and activated by BTK.…”
Section: The Role Of Melatonin In Allergic Reactions To Foodmentioning
confidence: 93%
“…The results showed that differentiated cells improved blood glucose levels due to insulin secreted by transplanted cells surviving in islets, while undifferentiated cells improved the inflammation milieu, but had only a slight effect on glucose levels. Recently, the combination of melatonin with WJ-MSCs was investigated in diabetic mice and the pre-treatment with melatonin alleviated blood glucose levels [ 107 ]. In another study, some decellularized matrices were used as a scaffold to support the differentiation of WJ-MSCs into IPCs.…”
Section: Perinatal Cellsmentioning
confidence: 99%